Let's solve your equation step-by-step.
3
−
2
x
+
3
x
=
5
−
2
(
2
x
−
3
)
Step 1: Simplify both sides of the equation.
3
−
2
x
+
3
x
=
5
−
2
(
2
x
−
3
)
3
+
−
2
x
+
3
x
=
5
+
(
−
2
)
(
2
x
)
+
(
−
2
)
(
−
3
)
(Distribute)
3
+
−
2
x
+
3
x
=
5
+
−
4
x
+
6
(
−
2
x
+
3
x
)
+
(
3
)
=
(
−
4
x
)
+
(
5
+
6
)
(Combine Like Terms)
x
+
3
=
−
4
x
+
11
x
+
3
=
−
4
x
+
11
Step 2: Add 4x to both sides.
x
+
3
+
4
x
=
−
4
x
+
11
+
4
x
5
x
+
3
=
11
Step 3: Subtract 3 from both sides.
5
x
+
3
−
3
=
11
−
3
5
x
=
8
Step 4: Divide both sides by 5.
5
x
5
=
8
5
x
=
8
5